Ketogenic-Diet Shake Containing Uncaria tomentosa-Associated Acute Interstitial Nephritis - Gilda Portalatin; Shruti Shettigar; Astrid Carrion-Rodriguez; Sushma Medikayala; Leal Herlitz; Dianne Sandy; Surafel K. Gebreselassie; Shane A. Bobart (Case Reports in Nephrology and Dialysis, 2022)
Uncaria tomentosa is a plant that has been used in traditional medicine for its anti-inflammatory, immunomodulatory, and immunostimulant properties. As a result, it can be found in several over-the-counter supplements worldwide. Acute interstitial nephritis (AIN) can be due to an offending medication, infection, or autoimmunity. We present a case of a patient who was on a strict ketogenic diet, utilizing over-the-counter diet shakes containing the herbal supplement Uncaria tomentosa who developed acute kidney injury with a serum creatinine of 3.6 mg/dL up from a baseline of 0.7 mg/dL. Serological evaluation was negative, and kidney biopsy revealed interstitial inflammatory infiltrates including focally prominent eosinophils and multifocal tubulitis. Stopping the keto-diet shake containing Uncaria tomentosa and concomitant corticosteroid therapy resulted in improvement in kidney function to near baseline. To our knowledge, this is the only biopsy-proven case of AIN in the setting of Uncaria tomentosa use.